2011
DOI: 10.3354/meps09024
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of bacterial communities in the mucus of Montastraea annularis

Abstract: Corals are known to contain a diverse microbiota; however, few studies have explicitly addressed the spatial variability of bacterial communities across individual, healthy coral colonies. This study applied culture-based and culture-independent methods to examine the spatial heterogeneity in bacterial communities in the mucus of 3 healthy Montastraea annularis colonies from Looe Key Reef, Florida Keys. Automated ribosomal intergenic spacer analysis (ARISA) results showed significant variability (up to 61% dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 80 publications
2
36
4
Order By: Relevance
“…1, panel II). As reported previously for other animals, most interactions between the potential colonizers and A. aurita appear to occur at the mucosal surface, forming a barrier against ambient seawater (59)(60)(61). The majority of bacteria identified on polyps by FISH analysis are Gammaproteobacteria, Tables 1 and 2 for alpha and beta diversity analyses, respectively.…”
Section: Discussionmentioning
confidence: 66%
“…1, panel II). As reported previously for other animals, most interactions between the potential colonizers and A. aurita appear to occur at the mucosal surface, forming a barrier against ambient seawater (59)(60)(61). The majority of bacteria identified on polyps by FISH analysis are Gammaproteobacteria, Tables 1 and 2 for alpha and beta diversity analyses, respectively.…”
Section: Discussionmentioning
confidence: 66%
“…We thus hypothesize that WP infection is only localized to the disease front, and that bleached and WP Diseased tissues are distinct in their viral composition. Bacteria associated with coral mucus have been shown to be spatially heterogeneous (Daniels et al, 2011), and here we demonstrate viral heterogeneity in a coral colony. Ultimately, we have shown that healthy corals have more abundant viral similarities to Herpesviridae, bleached corals possess more viral similarities to NCLDVs, such as Phycodnaviridae and Poxviridae, and diseased tissues contain an abundance of unique SCSDVs including members similar to Circoviridae and Nanoviridae, as well as their associated satellites; this novel SCSD viral group therefore may be responsible for WP infections in M. annularis.…”
Section: Discussionmentioning
confidence: 85%
“…The significance of the bacterial assemblage to the coral animal is not well understood, although coral bacteria have been characterized as species specific (1) and may have roles in nitrogen fixation, carbon fixation, antibiotic production, and other features that enable their health and functioning (1)(2)(3)(4)(5). A substantial component of the coral bacterial community resides within the mucus layer (6,7), and there is little understanding of which microbial partners are actually in residence within the coral tissues and potentially interacting with the coral. Here, we address this lack of knowledge by examining if and how a dominant group of bacteria frequently recovered in sequencing-based studies is located internally within the coral tissues of the Red Sea coral Stylophora pistillata.…”
mentioning
confidence: 99%